Analisis Kinerja Sektor Ekonomi Selama Pandemi Covid-19 di Kota Makassar - Nur Ilmiah Rivai; Muhammad Alfa Sikar; Inayatul Muthmainnah; Nursafitra M (Program Pascasarjana STIE Amkop Makassar, 2022)
Abstract This study aims to determine and analyze the influence of the performance of the economic sector during the Covid-19 pandemic in Makassar City. This research was conducted from June to August 2021 in Makassar City. Data analysis used descriptive statistical analysis and multiple regression analysis with the help of SPSS version 25.0. The population and sample in this study were employees affected by COVID-19 in Makassar City in the four sectors of hospitality, retail, restaurant and welding, totaling 200 people. Sample selection is done by using the sampling method. Based on the results of this study indicate that (Competency Training, Government Regulations) have an effect either partially or simultaneously on economic performance in Makassar City. Keywords: Training; Regulation; Economy;